Student Perspective on Practical Learning Method in Pandemic of COVID-19 - Harianto, Anton; Situmorang, Ringkar; Alexandra, Yoanita; Ardani, Edvi Gracia (ADI Publisher, 2021)
The Covid-19 pandemic has a wide and deep impact that has changed patterns of life and behavior both in the business sector and in daily human activities. One of the changing patterns of activity is in the education industry, many educational institutions across the world have closed due to this pandemic, and it could jeopardize the academic calendar. Most educational institutes have shifted to online learning platforms to keep academic activities going. However, the question about the preparedness, designing, and effectiveness of e-learning is still not clearly understood, particularly in Indonesia where the technical constraints like suitability of devices and bandwidth availability pose a serious challenge. This issue is even more challenging in the hospitality vocational education. This paper aims to dig deeper the online learning patterns in the perspective of the students in vocational education as the impact of the pandemic. This study uses a qualitative method by conducting in-depth interviews of 15 participants with the expected result to provide information that can help various parties, such as vocational institutions, teachers, and the hotel industry.